Core curriculum for maternal-newborn nursing - Mattson, Susan; Smith, Judy E. (Saint Louis, MO : Elsevier, 2016)
This text provides the most up-to-date, accurate information available on today's maternal-newborn nursing practice. Its concise outline format covers concepts of reproduction, fetal development, normal pregnancy, intrapartum and postpartum periods, the normal newborn, complications in the mother and newborn, and ethical issues. With a fresh focus on patient safety and revised case studies, this clinical guide and certification prep tool features AWHONN-endorsed content for the practice of maternal-newborn nursing.
Chapter 1 Reproductive anatomy, physiology, and the menstrual cycle -- Chapter 2 Genetics -- Chapter 3 Fetal and placental development and functioning -- Chapter 4 Perinatal cultural diversity -- Chapter 5 Physiology of pregnancy -- Chapter 6 Psychology of pregnancy -- Chapter 7 Age-related concerns -- Chapter 8 Antepartum fetal surveillance and prenatal diagnosis -- Chapter 9 Environmental hazards -- Chapter 10 Essential forces and factors in labor -- Chapter 11 Normal childbirth -- Chapter 12 Intrapartum fetal assessment -- Chapter 13 Physical and psychologic changes and childbirth -- Chapter 14 Breastfeeding -- Chapter 15 Contraception -- Chapter 16 Transitional care of the newborn -- Chapter 17 The infant at risk -- Chapter 18 Intimate partner violence -- Chapter 19 Hypertensive disorders in pregnancy -- Chapter 20 Maternal infections -- Chapter 21 Hemorragic disorders -- Chapter 22 Endocrine and metabolic disorders -- Chapter 23 Management of non-obstetrical surgery and trauma in pregnancy -- Chapter 24 Substance abuse in pregnancy -- Chapter 25 Other medical complications -- Chapter 26 Labor and delivery at risk -- Chapter 27 Postpartum complications -- Chapter 28 Ethics.
Includes bibliographical references and index.
Keywords: Education, Nursing; Maternal-child nursing -- Education